Extracellular Vesicles Derived From Canine Mesenchymal Stromal Cells in Serum Free Culture Medium Have Anti-inflammatory Effect on Microglial Cells - Kuwahara, Yukina; Yoshizaki, Karin; Nishida, Hidetaka; Kamishina, Hiroaki; Maeda, Sadatoshi; Takano, Katsura; Fujita, Naoki; Nishimura, Ryohei; Jo, Jun-ichiro; Tabata, Yasuhiko; Akiyoshi, Hideo (Frontiers in Veterinary Science, 2021)
Mesenchymal stem/stromal cells (MSCs) have been used as cell sources for treating dogs with naturally-occurring diseases. Extracellular vesicles (EVs) derived from MSCs are now recognized as pivotal to modulating the immune response and supporting tissue repair. Manufacture of MSC-EVs for clinical application mandates removal of the xeno-proteins, including fetal bovine serum. The objective of this study was to examine whether canine MSCs survived and secreted EVs in serum-free medium (SFM) conditions and to assess the immunomodulatory effect of EVs in vitro. Canine MSCs were found to survive and secrete EVs under SFM conditions. The surface markers of MSCs in the SFM were similar to MSCs in complete culture medium. Canine MSC-EVs had a diameter of approximately 300 nm and were positive for EV markers. MSC-derived EVs from the serum-free condition reduced the levels of IL-1b by BV-2 cells in response to LPS stimulation. These results warrant further studies of the use of SFM for producing EVs derived from canine MSCs.